Internal jugular vein tumor thrombus in papillary thyroid cancer: our institution’s experience and a systematic review of the literature - Laurin, Bryce J.; Ballard, Robert; Malik, Ifthikar; Mitchell, Janeil (Frontiers in Endocrinology, 2025)
Papillary thyroid tumor thrombosis of the internal jugular vein (IJV) is a rarely observed phenomenon with fewer than 30 cases reported to date. The clinical features and underlying pathogenesis of tumor thrombosis are not well-elucidated. A PRISMA-compliant systematic review was conducted, yielding 20 studies eligible for analysis. Additionally, we describe a case of papillary thyroid cancer (PTC) tumor thrombus involving the IJV with solitary metastasis to the ipsilateral kidney. The majority of patients in the cohort presented in an asymptomatic state (n = 14) with variable timepoints in diagnosis: preoperative (n = 9), intraoperatively (n = 1), and postoperative period (n =11), up to 30 years post-thyroidectomy. Primary tumor sizes ranged widely, with a mean of 4.22 cm ± 2.64cm. Most patients (85.7%) presented with nodal involvement and a few (n =4) had distant metastases with pulmonary involvement most commonly reported. Open tumor thrombectomy was performed in 10 (52.6%) cases and extensive vascular reconstruction was required in 8 (42%). Adjuvant treatment including radioactive iodine ablation (36.8%) and external beam radiation (21.1%) was also employed. Patient clinical factors, presentation, diagnosis, and management of PTC vascular tumor thrombus are heterogeneous. Tumor thrombus occurred in patients with solitary, small primary tumors and patients with heavy locoregional disease burden and presents as isolated and extensive thrombotic burden, the latter requiring complex open cardiovascular reconstruction in some patients. The rarity of the disease and diverse clinical presentation reporting remains a challenge in the understanding of pathogenesis, optimal management, and outcomes in PTC-related thrombosis.